Crisis and precariousness in COVID-19 times - Santos, Miriam de Oliveira; de Mesquita, Jacqueline Lobo (Pontifícia Universidade Católica de São Paulo, 2021)
The aim of this article is to reflect on the workers' ability to mobilize despite the increase in job insecurity and social inequality due to the COVID-19 pandemic. We compared the bibliographic review with an analysis of news on the movements of app delivery workers and pointed out as provisional conclusions that, despite all the predictions that pointed to the precariousness of work as a practice that would lead to the end of the social mobilization of workers, that was not what occurred.